Faktor-faktor yang Mempengaruhi Minat Mahasiswa Berinvestasi di Bursa Efek Indonesia - Asari, Asari; Triyono, Agus; Lubis, Riyani Fitri (JYRS: Journal of Youth Research and Studies, 2024)
The Investment Gallery of the Indonesia Stock Exchange (IDX) serves as a means of introducing the Capital Market to the academic world. The IDX is a collaboration between universities and securities companies, aiming to introduce the Capital Market from both theoretical and practical perspectives. A common social phenomenon is where individuals are influenced to make decisions because others in their environment are doing so. This phenomenon frequently occurs in the investment world, where investors follow the actions of other investors despite having limited knowledge and information. The lack of interest in investing is due to two factors, namely knowledge and motivation to invest. This research is quantitative, utilizing a quantitative approach which is a method to test specific theories and can be conducted by examining the relationships between variables. The data collection techniques used include observation, questionnaires, and documentation. The sample size used in this study is 91 respondents. The data analysis techniques used are validity tests, reliability tests, classical assumption tests, and hypothesis testing. Firstly, the results of this study indicate that partially, the investment knowledge variable, with a significance level of 0.020 < 0.05 and a t-value of 2.371, compared to the t-table value of 1.661, shows that t-value 2.371 > t-table 1.661, has a positive and significant effect on the interest in investing among students of the Faculty of Sharia and Islamic Economics at the Indonesia Stock Exchange. Secondly, the motivation variable shows that partially, the motivation variable, with a significance level of 0.000 < 0.05 and a t-value of 6.028, compared to the t-table value of 1.661, shows that t-value 6.028 > t-table 1.661, has a positive and significant effect on the interest in investing among students of the Faculty of Sharia and Islamic Economics at the Indonesia Stock Exchange. Thirdly, simultaneously, the investment knowledge and motivation variables have a positive and significant effect with a significance level of 0.000 < 0.05 and an F-value of 96.812 > F-table 3.10. Therefore, it can be concluded that the investment knowledge and motivation variables have a positive and significant effect on students' interest in investing in the Indonesia Stock Exchange by 68.0%, while the remaining 32.0% is influenced by other variables not examined in this study.